Infrastructure, Growth, and Inequality : An Overview - Calderon, Cesar (World Bank Group, Washington, DC, 2014)
Academics and policy makers have long considered an adequate supply of infrastructure services to be essential for economic development. This paper reviews recent theoretical and empirical literature on the effects of infrastructure development on growth and income distribution. The theoretical literature has employed a variety of analytical settings regarding the drivers of income growth, the degree to which infrastructure represents a public or a private good, and the extent of market distortions, notably in capital markets. In turn, the empirical literature has used various econometric methodologies on time-series and cross-section macro and microeconomic data to test for the effects of infrastructure development. However, these empirical tests face challenging issues of measurement, identification, and heterogeneity. Overall, the literature finds positive effects of infrastructure development on income growth and, more tentatively, on distributive equity. Still, the precise mechanisms through which these effects accrue, and their full impact on welfare, remain relatively unexplored.